Efektivitas Perlakuan Kombinatif Plasma Medis dan Ekstrak Daun Sirih untuk Mempercepat Penyembuhan Luka Fase Proliferasi pada Model Mencit Diabetik - Wahyuningtyas, Eka Sakti; Nasruddin, Nasruddin; Rahayu, Heni Setyowati Esti; Lutfiyati, Heni; Sikumbang, Isabella Meliawati; Nurani, Laela Hayu; Rohmani, Afiana; Salsabila, Nia; Putri, Gela Setya Ayu (LPPM STIKES MUHAMMADIYAH GOMBONG, 2019)
The continued increase in the number of people with Diabetes Mellitus (DM) in Indonesia is a serious problem. One of the big problems for people with Diabetes Mellitus (DM) is the emergence of complications of diabetic wounds. To date the strategy for treatment of diabetic wounds has been limited to the use of wound dressing, cell therapy and oxygen therapy. The problem is that the strategy is not fully successful. Thus, it is very important to look for new strategies to improve the quality of diabetic wound healing, such as by applying a combination of plasma medicine and local natural product, like the extraction of Daun sirih (Piper betle) leaves. Plasma medicine is a relatively new and multidisciplinary study involving plasma science, biomedical, pharmaceutical and other health sciences aimed at applying plasma to therapeutic health. Plasma is the fourth phase of matter, after the solid, liquid and gas phase. The medical aspects of plasma are related to the ability of plasma to produce biological molecules Reactive Oxygen and Nitrogen Species (RONS). If RONS is controlled in the right dosage it can be efficacious for health therapy. This study intends to examine the effects of combinative treatment of plasma medicine and Piper betel leaf extract for proliferation phase of wound healing in diabetic small animal model. This study used male Balb c mice with acute wounds which were divided into 5 groups, namely groups of untreated normal mice (ND-TP), groups of untreated diabetic mice (D-TP), groups of diabetic mice wounds with Piper betel leaf extract (DS ), the wound group of diabetic mice with plasma medicine (DP) and the wound group of diabetic mice with plasma medicine and Piper betel leaf (DPS). The plasma medicine was treated on wound with condition non-contact style (the plasma jet did not touch the wound) with a distance of plasma jet reactor nozzle to the surface of wound about 20 mm, for 2 minutes, every day. Macroscopic observation of wounds is carried out every day from day 0 to 7. On day 7 it was seen that the size of the wound area for D-P-S was smaller than the other groups. The results of this study indicated that Piper betel leaf extract can potentially be used to optimize the performance of plasma medicine in accelerating diabetic wound healing during the proliferation phase. Further investigation, however, is important to be conducted to study the effect for all phases of wound healing and its mechanism histo-pathologically.